2013
DOI: 10.4236/as.2013.49b015
|View full text |Cite
|
Sign up to set email alerts
|

Base-transesterification process for biodiesel fuel production from spent frying oils

Abstract: The concept of converting recycled oils to clean biodiesel aims towards reducing the amount of waste oils to be treated and lowering the cost of biodiesel production. Samples of waste oils were prepared from Spent Frying oil collected from local hotels and restaurants in Khartoum, Sudan. Selected methods to achieve maximum yield of biodiesel using the waste feedstock were presented and compared. Some properties of the feedstock, such as free fatty acid content and moisture content, were measured and evaluated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(47 citation statements)
references
References 2 publications
0
1
0
3
Order By: Relevance
“…The fatty acid composition, especially the contents of C16:0 and C18:1, were also enhanced after the microwave and sonication pre-treatments in algal species [131]. Enhancement of the lipids extracted from algal species improved the cetane number, high heating value, cold filter plugging point, and oxidative stability as compared to controls [131][132][133][134][135][136][137][138][139][140][141][142][143][144][145][146][147][148][149][150]. The results of this study confirmed that the conversion of biofuels from algae could be increased by the ultrasound and microwave techniques, to develop an eco-green and sustainable environment .…”
Section: Algal Resourcesmentioning
confidence: 99%
“…The fatty acid composition, especially the contents of C16:0 and C18:1, were also enhanced after the microwave and sonication pre-treatments in algal species [131]. Enhancement of the lipids extracted from algal species improved the cetane number, high heating value, cold filter plugging point, and oxidative stability as compared to controls [131][132][133][134][135][136][137][138][139][140][141][142][143][144][145][146][147][148][149][150]. The results of this study confirmed that the conversion of biofuels from algae could be increased by the ultrasound and microwave techniques, to develop an eco-green and sustainable environment .…”
Section: Algal Resourcesmentioning
confidence: 99%
“…La información usada se obtuvo de una recopilación de diferentes proyectos de producción de biocombustibles. Los datos asociados se caracterizan por ser biodiesel obtenidos a través de transesterificación, la cual inició con E. Duffy y J. Patrick a mitad del siglo XIX [10] este proceso es una reacción química de un aceite o grasa vegetal con un alcohol.…”
Section: A Parámetros Iniciales Y Condiciones Generalesunclassified
“…Esta estimación se produjo a través de la comparación de los valores recolectados de autores como Vivas [1], García [5], Blanguino & Romano [6], Abdalla [10], y ASTM D6751 [11], entre otros, teniendo presente el cumplimiento de rangos teóricos y de las mismas fuentes con el fin de comprender el comportamiento de un biodiesel de acuerdo a su composición química, esto se evaluó empleando MatLab para el desarrollo de las ecuaciones, teniendo presente que de los modelos consultados solo se valoraron los parámetros definidos en la metodología (Densidad, Capacidad calorífica, Viscosidad cinemática, Gravedad API, Poder calorífico superior y Número de Cetano), debido a la información disponible en la red y los resultados teóricos que arrojaron en una primera etapa donde solo esos parámetros mostraron ser consistentes con resultados obtenidos en trabajos similares.…”
Section: Poder Caloríficounclassified
See 1 more Smart Citation
“…K. Abdalla et al 2013 [3]in this paper gives a clear idea about concept of biodiesel production from fired cooking oil. The aim of use this oil because it reduce the cost the price of the production of biodiesel because it is obtained chiefly from local hotels, catering services, cafeteria etc, .he gives the result as biodiesel yield is 92% and it is depends on the quality of the collected raw oil, kinematic viscosity is 5.5091 mm 2 s -1 at 40 0 c, flash point 174 0 c and cetane number is 4820.…”
mentioning
confidence: 93%